A microsimulation model of labour supply for UK tax reform - Alan S. Duncan (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1991)
In this paper, we estimate a theory-consistent model of single parents labour supply behaviour using a variant of the semi-log labour supply function. The underlying preferences are used to simulate the impact of a proposed reform to the Family Credit element of the UK Social Security system using the simulation algorithm SPAIN (Simulation Program for the Analysis of INcentives). In choosing an appropriate labour supply model to include in the simulation algorithm, the degree to which the model satisfies concavity is an important distributional consideration. In this respect, the semi-log supply function is found to be a most suitable model for simulation, with virtually the entire sample of single parents satisfying the Slutsky condition both at the estimation stage and during simulation. Using data from the UK Family Expenditure Survey over the years 1981 to 1988, a model of labour force participation is developed. Empirical results indicate that the presence of a young child in the household is the single most important factor discouraging labour market participation. The availability of both formal and informal childcare are seen to raise the probability of participation. Results from our simulation suggest that between 30,000 and 40,000 lone parents will be encouraged to return to work by the changes to Family Credit regulations, emphasising the potential positive labour market role of social security benefits.
Keywords: 330; Simulation; Arbeitsangebot; Alleinerziehende; Steuerreform; Großbritannien